Some aspects of the insect ecology of citrus orchards - Smithers, Courtenay Neville (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1954)
After a brief introduction, the species of Citrus on which the investigations were carried out are mentioned. This is followed by an account of the methods of collection used, and a discussion of their relative merits. The main method used was that in which the trees were fumigated with hydrocyanic acid gas, and the insects falling from the trees were taken up on sheets. The location of the areas where collections were made are then given. An annotated list of the species taken by the fumigation method follows, and the numerical data obtained at the same time regarding the species present is given in an abbreviated form and discussed. A more detailed discussion of the relative abundance of the species is then undertaken. The discussion of the ecology of the insects commences with the insects listed according to their activities, so far as known, and an account of five trees of striking faunal differences is given. A broader discussion of citrus ecology is then given, based on the data previously presented; this ends with a short reminder of the inherent 'oneness' of the insect with its environment.
Keywords: Citrus -- Diseases and pests; Insect pests